2000
DOI: 10.1002/(sici)1097-4555(200004)31:4<331::aid-jrs546>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular hydrogen abstraction from triplet excited state of decafluorobenzophenone: a Raman investigation

Abstract: The influence of the structure of the triplet excited state of benzophenone (bp) and decafluorobenzophenone (dfbp) on the reactivity towards hydrogen abstraction was studied by time-resolved resonance Raman spectroscopy. The resonance Raman spectra and Raman excitation profiles were recorded for both the triplet excited state and the ketyl radical. Vibrational spectral assignments were made for all the intermediate states.Based on the analysis of the spectra, it was concluded that the enhanced reactivity towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
(27 reference statements)
4
14
0
Order By: Relevance
“…36 The peak position concurs with the reported value. 31 With increasing temperature, the band center shifts to a lower frequency and the bandwidth shows broadening. The S/N ratio at the elevated temperature is decreased.…”
Section: Time-resolved Resonance Raman Spectra Of Dfbpkmentioning
confidence: 99%
See 1 more Smart Citation
“…36 The peak position concurs with the reported value. 31 With increasing temperature, the band center shifts to a lower frequency and the bandwidth shows broadening. The S/N ratio at the elevated temperature is decreased.…”
Section: Time-resolved Resonance Raman Spectra Of Dfbpkmentioning
confidence: 99%
“…The peak position concurs with the reported value. 31 As shown in Figure 2b, with increasing temperature the band shifts to a lower frequency, while the band shape does not show significant temperature dependence. We estimated the peak position and the bandwidth of this mode by fitting the Raman band to a Gaussian function.…”
Section: Time-resolved Resonance Raman Spectra Of Dfbpkmentioning
confidence: 99%
“…In this work, conventional Raman and time‐resolved resonance Raman spectroscopy (TR 3 ) techniques were used to examine the ground and the triplet excited states structure, respectively. TR 3 spectroscopy is a powerful technique to elucidate the vibrational structure of the transient species . When the Raman excitation wavelength is in resonance with an allowed electronic transition of the molecule, the Raman peaks coupled to the chromophore become enhanced, accounting for the high sensitivity and selectivity of the technique .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, electron‐withdrawing groups generally increase the photoreduction ability of substituted BP triplet states. The decafluoro‐BP derivative was found to be 10–40 times more reactive than the parent BP molecule, and the hydrogen abstraction rate of the triplet 4‐trifluoromethylacetophenone molecule is six times faster than the parent acetophenone molecule…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, electronwithdrawing groups generally increase the photoreduction ability of substituted BP triplet states. The decafluoro-BP derivative was found to be 10-40 times more reactive than the parent BP molecule, [19,20] and the hydrogen abstraction rate of the triplet 4-trifluoromethylacetophenone molecule is six times faster than the parent acetophenone molecule. [21] Some studies reported for the photochemistry and photophysics of BP determined that the energy gap of the lowest excited singlet state (S 1, np*) and the second triplet state (T 2, pp*) is fairly small and the spin-orbit coupling between these two states is allowed.…”
Section: Introductionmentioning
confidence: 99%